(untitled) (Proceedings of the International Conference on Food, Nutrition, Health and Lifestyle, 2024)
: Fermented rice called “Khao-Mak” is one of the most popular traditional foods in Thailand. Khao-Mak is low in protein and fiber content. This study aimed to evaluate the possibility of using quinoa as a functional ingredient in Khao-Mak. Five formulas of Khao-Mak were prepared by replacing waxy rice with quinoa at 0, 30, 50, and 100 % were fermented using the traditional starter culture (Look-Pang powder) (2% of the mixture). The proximate compositions, physical characteristics, and sensory evaluation of Khao-Mak were determined. The result revealed that the waxy rice could be replaced by quinoa in Khao-Mak for up to 30%. The fermented time was one day comparable to a Kho-Mak without adding quinoa and commercial formula. The appearance of Khao-Mak with 30% quinoa addition had good clump, light yellow, good odor, and soft texture with a small amount of water syneresis called “Nam-Toy”. The pH, total soluble solid, and reducing sugar of Khao-Mak with 30% quinoa were 3.46, 27 °brix, and 24.86 mg/g, respectively. The sensory scores of Khao-Maks with 30% quinoa were no significant difference compared with the 0% quinoa and commercial formula. The protein and dietary fiber content of Khao-Mak (30% quinoa) increased from 4.30% (control) to 11.86% for protein and from 0.1% to 4.02% for dietary fiber. This study suggested that quinoa could be used as a source of protein, fiber, and a functional ingredient in Khao-Mak preparation that could provide a high nutritional value for the health benefits of a traditional sweet dessert.